SYSTEM OF STATISTICAL ANALYSIS OF ANGULAR DATA IN THE ENVIRONMENT LabVIEW - Куц, Ю. В.; Канівець, І. А. (Science-based technologies, 2009)
To сonsider a problems of definition of selected statistics characteristics of a random angles. Created a programmatic module for definition of numerical characteristic of a random angles environment LabVIEW.